Formation of the concept, features and characteristics of the period of formation and development of executive power in Ukraine - Dneprov, Oleksii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article explores scientific views on the formation and becoming of the principle of separation of powers. The definition and concepts of power formation have been analyzed. A number of generalizing features of executive power have been singled out. Functional and organizational and legal characteristics of the executive power are considered. It has been noted that the executive branch as a function is associated with public administration in the narrow sense. It has been determined that the executive power as an organization is a set (system) of state bodies and officials who perform the relevant function at the political (primarily government and, to varying degrees in different forms of government, head of state) and administrative (public administration) levels.It is established that the executive power is a kind of state power, so it has the right to inherit all the features and characteristics that are characteristic of the generic concept of "power" in general. Along with this essence and legal significance for social existence, state power is characterized by the fact that it carries out management activities by society. For this purpose, it has a special holistic professional apparatus that performs tasks and functions in various areas assigned to them by law. The defined system of public authorities has broad powers and represents the state, as it is authorized to act on its behalf. The effectiveness of the system of executive bodies depends on how it is distributed among the relevant state bodies and on the principles of its implementation; today there are two priority areas for improving the implementation of executive power: first, the structural improvement of the branches of government, ie the creation of an optimal structure in each industry); secondly, the improvement of the powers exercised by these bodies (by way of their clearer distribution, consolidation and improvement of the conditions and procedure for their implementation).